Exploring the Healthcare and Socio-economic Challenges Confronted by Retired Employees in Karachi (Journal of Social Sciences Review, 2025)
This study explores the healthcare and socio-economic challenges that retired employees face in Karachi, Pakistan. Using a mixed-methods approach, it combines quantitative data analysis through SPSS with qualitative insights to gain a deeper understanding of these complex issues. The research aims to identify key challenges, test relevant hypotheses, and offer practical recommendations. Data was gathered through surveys and interviews, then analyzed using frequency and percentage calculations, along with chi-square tests to examine relationships between variables. The findings highlight major concerns such as limited access to healthcare, financial instability, and social isolation. Based on these insights, the study provides recommendations for policymakers, healthcare providers, and community organizations to help improve the well-being of retired individuals.
Keywords: Retirement Challenges; Geriatric Healthcare; Pension Security; Socioeconomic Well-being